2002
DOI: 10.1021/ma020260w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfonated Polyimides as Polyelectrolytes for Fuel Cell Application. 2. Synthesis and Proton Conductivity of Polyimides from 9,9-Bis(4-aminophenyl)fluorene-2,7-disulfonic Acid

Abstract: A new sulfonated diamine monomer, 9,9-bis(4-aminophenyl)fluorene-2,7-disulfonic acid (BAPFDS), was synthesized by direct sulfonation of the parent diamine, 9,9-bis(4-aminophenyl)fluorene (BAPF), using fuming sulfuric acid as the sulfonating reagent. A series of sulfonated polyimides with different sulfonation degrees were prepared from 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA), BAPFDS, and common nonsulfonated diamines. The resulting sulfonated polyimides generally showed good solubility in m-creso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
226
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(235 citation statements)
references
References 12 publications
7
226
0
2
Order By: Relevance
“…While some available diamines could be theoretically sulfonated, only a few diamine monomers containing -SO 3 H groups have been successfully obtained for the preparation of SPIs due to the complexity of the sulfonation reaction [16,[21][22][23][24][25][26]. Thus, it is important to explore further approaches to incorporate -SO 3 H groups into diamines.…”
Section: Synthesis and Characterization Of Sulfonated Diamine Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…While some available diamines could be theoretically sulfonated, only a few diamine monomers containing -SO 3 H groups have been successfully obtained for the preparation of SPIs due to the complexity of the sulfonation reaction [16,[21][22][23][24][25][26]. Thus, it is important to explore further approaches to incorporate -SO 3 H groups into diamines.…”
Section: Synthesis and Characterization Of Sulfonated Diamine Monomersmentioning
confidence: 99%
“…Mercier and co-workers reported the synthesis of a series of SPIs from 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA) and the results indicated that NTDA-based six-membered ring polyimides were more stable than five-membered ring PIs under fuel-cell conditions [15]. Okamoto and co-workers reported several series of SPIs based on sulfonated diamines and NTDA, some of which exhibited good fuel cell properties [22][23][24][25][26]. For example, sulfonated diamine monomers with flexible linkages, 4,4 ′ -diaminodiphenylether-2,2 ′ -disulfonic acid (ODADS) or 9,9-bis(4-aminophenyl)fluorene-2,7-disulfonic acid (BAPFDS) led to ODADS or BAPFDS-based polyimides that exhibited much better water stability than those derived from a widely used sulfonated diamine, 2,2 ′ -benzidinedisulfonic acid [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Sulfonated polyimide copolymers have been proposed by several research groups. [6][7][8][9][10][11][12][13][14][15][16][17] The advantage of polyimide ionomers is that a high-molecular-weight polymer with good film-forming capability and high mechanical strength can be easily synthesized by the polycondensation of sulfonated diamine monomers. The hydrophilic/hydrophobic balance or ion-exchange capacity (IEC) can be controlled by changes in the copolymer composition.…”
Section: Introductionmentioning
confidence: 99%
“…The first one consists in replacing Nafion ® by alternative polymers, such as sulfonated polyetherketone [2], sulfonated polysulfone [3,4], sulfonated aromatic polyimide [5,6] and polybenzimidazole (PBI) doped by a strong acid, e.g., H 3 PO 4 and H 2 SO 4 [7,8]. PBI membranes are remarkable because they do not need permanent hydratation for exhibiting high ionic conductivity, which makes their use at temperatures higher than 100°C feasible.…”
Section: Introductionmentioning
confidence: 99%